Para-Axillary Subcutaneous Endoscopic Approach in Torticollis: Tips and Tricks in the Surgical Technique - Tokar, Baran; Karacay, Safak; Arda, Surhan; Alici, Umut (European Journal of Pediatric Surgery, 2015)
Aim An obvious scar on the neck may appear following the open surgery for congenital muscular torticollis (CMT). The cosmetic result may displease the patient and the family. In this study, we describe a minimally invasive technique, para-axillary subcutaneous endoscopic approach (PASEA) in CMT.Patients and Methods A total of 11 children (seven girls and four boys with the age range between 1 and 15 years) were operated for torticollis by PASEA. All patients had facial asymmetry and head and neck postural abnormality. Following an incision at the ipsilateral para-axillary region, a subcutaneous cavernous working space is formed toward sternocleidomastoid (SCM) muscle. The muscle and fascia are cut by cautery under endoscopic vision. The patients had postoperative 2nd-week and 3rd-month visits. The incision scar, inspection, and palpation findings of the region, head posture, and shoulder position of the affected side were considered in evaluation of the cosmetic outcome. Preoperative and postoperative range of motion of the head and neck were compared for functional outcome.Results We preferred single incision surgery in our last two patients; the rest had double para-axillary incision for port insertion. Incomplete transection of the muscle was not observed. There was no serious complication. Postoperatively, head posture and shoulder elevation were corrected significantly. Range of motion of the head was improved. Postoperatively, all the patients had rotation capacity with more than 30 degrees. The range of postoperative flexion and extension movements was between 45 and 60 degrees.Conclusions The open surgery techniques of CMT causes visible lifelong incision scar on the neck. PASEA leaves a cosmetically hidden scar in the axillary region. A single incision surgery is also possible. A well-formed cavernous working space is needed. External manual palpation, delicate dissection, and cutting of SCM muscle with cautery are the important components of the procedure. Surgeons having experience in pediatric minimal invasive surgery may consider PASEA as an alternative to the open approach in CMT. The surgeon should be familiar with surgical anatomy of the neck and must be highly competent in management of possible complications in the region.
Keywords: torticollis; laparoscopy; endoscopy; neck; children